3D printing in orthopaedic surgery: a scoping review of randomized controlled trials. Issue 12 (1st December 2021) - Wong, Ronald Man Yeung; Wong, Pui Yan; Liu, Chaoran; Chung, Yik Lok; Wong, Kwok Chuen; Tso, Chi Yin; Chow, Simon Kwoon-Ho; Cheung, Wing-Hoi; Yung, Patrick Shu-Hang; Chui, Chun Sing; Law, Sheung Wai
Abstract : Aims: The use of 3D printing has become increasingly popular and has been widely used in orthopaedic surgery. There has been a trend towards an increasing number of publications in this field, but existing literature incorporates limited high-quality studies, and there is a lack of reports on outcomes. The aim of this study was to perform a scoping review with Level I evidence on the application and effectiveness of 3D printing. Methods: A literature search was performed in PubMed, Embase, and Web of Science databases. The keywords used for the search criteria were ((3d print*) OR (rapid prototyp*) OR (additive manufactur*)) AND (orthopaedic). The inclusion criteria were: 1) use of 3D printing in orthopaedics, 2) randomized controlled trials, and 3) studies with participants/patients. Risk of bias was assessed with Cochrane Collaboration Tool and PEDro Score. Pooled analysis was performed. Results: Overall, 21 studies were included in our study with a pooled total of 932 participants. Pooled analysis showed that operating time (p < 0.001), blood loss (p < 0.001), fluoroscopy times (p < 0.001), bone union time (p < 0.001), pain (p = 0.040), accuracy (p < 0.001), and functional scores (p < 0.001) were significantly improved with 3D printing compared to the control group. There were no significant differences in complications. Conclusion: 3D printing is a rapidly developing field in orthopaedics. Our findings show that 3D printing is advantageous in terms of operating time, blood loss, fluoroscopy times, bone union time, pain, accuracy, and function. The use of 3D printing did not increase the risk of complications. Cite this article: Bone Joint Res 2021;10(12):807–819.